Integrative Analysis of Retusa pertenuis (Heterobranchia: Cephalaspidea) from Arctic and Russian Far East Seas with Discussion of Its Morphology, Validity and Population Structure - Elena Chaban; Irina Ekimova; Maria Stanovova; Dimitry Schepetov (Diversity, 2023)
Retusa pertenuis is still formally considered a junior subjective synonym of Retusa obtusa, despite previous data indicating R. pertenuis and R. obtusa differ significantly in copulatory system morphology. In this paper, we study the species identity and population structure of R. pertenuis with an integrative approach combining morphological and molecular data. The external morphology, head copulatory system and gizzard plates were studied using light microscopy and scanning electron microscopy. We also obtained two mitochondrial (COI and 16S) and two nuclear (H3 and 28S) markers to test the monophyly of R. pertenuis and R. obtusa. Populations from the White Sea, Sea of Okhotsk and Sea of Japan were studied using COI and 18S molecular markers. Our results show that Retusa obtusa sensu lato represents a species complex of at least four species: the nominative species occurring in the North Atlantic, the widely distributed R. pertenuis and two additional species whose identities should be clarified in further studies. Retusa pertenuis geographic range encompasses the North Atlantic, Eurasia’s northern seas, the Canadian Arctic, the Bering Sea, the Sea of Okhotsk and the Sea of Japan. Within R. pertenuis’s range, this species demonstrates a wide variability in shell morphology.